This Hard Place and that Hard Terrain: Emerging Perspectives on Media and Cultural Studies on or in Zimbabwe - Mhiripiri, Nhamo Anthony (Palgrave Macmillan, 2021)
Zimbabwe has produced an exceptional number of post-graduate journalism, media and cultural studies scholars of note since the mid-1990s. Many amongst those prominent from the first generation of these scholars spent their formative years at the University of Zimbabwe (UZ) before migrating to European, South African and American universities. A considerable number attained (post-)doctoral qualifications during the so-called crisis years that coincide with former President Robert Mugabe and his ruling Zimbabwe African National Union (Patriotic Front)’s (ZANU-PF) land reform, ostensibly to correct historical colonial injustices of land dispossession. The land policy, amongst other factors, triggered economic decline (Bond & Manyanya, 2003). Local and international critics accused Mugabe’s government of political repression, including human and media rights violations; culminating in the imposition of targeted sanctions on Zimbabwe by the UK, the USA, the European Union, and many other Western countries. This chapter is an evaluative treatment of the work of UZ media studies graduates who became prominent media and cultural scholars on Zimbabwean media and cultural phenomena after graduating since 1993. Many of these young scholars left the country for greener pastures or to escape the decline, and to work in the diaspora.